Optimalisasi Manajemen Boarding School Dalam Mengembangkan Karakter Santri - Hayya Annisa Fitriani; Wahyono wahyono (Oasis : Jurnal Ilmiah Kajian Islam, 2025)
This study uses qualitative research methods with data collection techniques through in-depth interviews, in-depth observation and documentation. The research conducted an analysis using several stages, namely: data collection, data reduction, data presentation and then drawing conclusions. The results of this study are: (1) Planning, namely preparing program implementation documents, there is a schedule of student activities, monthly and annual student programs, (2) Implementation of the program at SMA Prakarya Santi Asromo by creating a program to familiarize students with daily routines, then there are tahfiz and language programs. As well as accustoming children to being orderly, disciplined, independent and responsible (3) Evaluation, program assessment with students once a week, then monthly and weekly meetings are always held with ustadz and ustadzah, and there are cottage report cards in which there is a value for students' character development for one semester